A case study about working with imagery in music therapy process - Rand, Pille (2014)
Music therapy can be broadly divided into active and receptive forms. Active music therapy deals mostly with different forms of improvisations and music making. Receptive music therapy deals with different forms of music listening. For example listening to music in a relaxed state might bring to listener’s mind images or sequences of images, experiences of bodily sensations or feelings. When discussing them afterwards, or by making them more visible in form of a drawing these images might resemble person’s dreams, wishes, thoughts or feelings. When working with them in more depth, it can give the person new insights, ideas and thoughts about their life situations and issues they might be dealing with. The current research narrative is a case study which analyses the episodes that are dealing with working with imagery in a music therapy setting with a 25 year old woman. The research done on the client’s imagery and discussions about it shows her overall processes and issues during that period of time as well as changes in them over time. It was interesting to see the reoccurring images and themes that reflected the client’s overall issues and after writing them out as well as categorizing them to see links and changes that had taken place, in the form of imagery as well as in her life.